An echocardiographic study comparing male Swedish elite orienteers with other elite endurance athletes - Henriksen, E.; Landelius, J.; Wesslen, L.; Kangro, T.; Jonason, T.; Nystrom-Rosander, C.; Niklasson, U.; Arnell, H.; Rolf, C.; Hammarstrom, E.; Lidell, C.; Ringqvist, I.; et al. (The American Journal of Cardiology, 1997)
Between 1979 and 1992, there were 16 known cases of sudden unexpected cardiac death among young Swedish orienteers, whose autopsies showed myocarditis to be a common finding. Therefore, 96 elite orienteers and 47 controls underwent echocardiography, showing left ventricular wall motion abnormalities in 9% of the orienteers compared with 4% in the controls.